Are We in This Together? Why Embracing Aspects of Child Care in School Is Vital to Reimagining Education (LEARNing Landscapes, 2023)
Child care and school are similar and interrelated, yet the comparison of school to child care seems contentious. The Covid-19 pandemic revealed pressure points in labeling these educational and care institutions essential—or not. This paper encourages collaboration between schools and child care as a vital component to reimagining education.
Keywords: child care; teachers not babysitters; early childhood education; early years; Covid-19